2014
DOI: 10.1016/j.fitote.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis C virus replication by chalepin and pseudane IX isolated from Ruta angustifolia leaves

Abstract: Hepatitis C virus (HCV) infection is highly prevalent among global populations, with an estimated number of infected patients being 170 million. Approximately 70-80% of patients acutely infected with HCV will progress to chronic liver disease, such as liver cirrhosis and hepatocellular carcinoma, which is a substantial cause of morbidity and mortality worldwide. New therapies for HCV infection have been developed, however, the therapeutic efficacies still need to be improved. Medicinal plants are promising sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 50 publications
0
62
0
1
Order By: Relevance
“…What is more, these compounds were more active than ribavirin, the standard used in treatment. The IC 50 of γ-fagarine (3) was 20.4 μg/ml, but it was 2.8 μg/ml for ribavirin and 6.4 μg/ml for kokusaginine (13) [34].…”
Section: The Biological Activity Of Furoquinoline Alkaloidsmentioning
confidence: 97%
“…What is more, these compounds were more active than ribavirin, the standard used in treatment. The IC 50 of γ-fagarine (3) was 20.4 μg/ml, but it was 2.8 μg/ml for ribavirin and 6.4 μg/ml for kokusaginine (13) [34].…”
Section: The Biological Activity Of Furoquinoline Alkaloidsmentioning
confidence: 97%
“…To firmly establish the antiviral activity and adverse reactions like reactogenecity or toxicity of the purified phytomolecules, appropriate in vivo studies (animal models) and subsequent clinical trials are necessary. A bioactive flavonoid 'Baicalein' isolated from Chinese medicinal plant Scutellaria baicalensis Georgi showed antiviral properties using high-speed counter-current chromatography (HSCCC) technique [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Antiviral Molecules Of Plant Originmentioning
confidence: 99%
“…Time of addition experiment revealed that the extract inhibited both at the entry and postentry steps. T. sureni leaves extract was not toxic (cytotoxicity concentration [CC 50 ]>500 µg/ml, SI>35.9); therefore, further study was taken to investigate the active substances from T. sureni leaves extract [13].…”
Section: Hafid Et Almentioning
confidence: 99%
“…The stock solutions were stored at −20°C until they were used. Analysis of anti-HCV method was described previously [9,13]. Huh-7.5 cells were seeded in 24-well plates (cell density 1.9×10 5 cells/well).…”
Section: Analysis Of Anti-hcv Activitiesmentioning
confidence: 99%